2007
DOI: 10.1111/j.1572-0241.2007.01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis-C Patients Have Reduced Growth Hormone (GH) Secretion Which Improves During Long-Term Therapy With Pegylated Interferon-α

Abstract: GH insufficiency is common in patients with chronic HCV infection. While GH secretion improves during antiviral therapy, IGF-1 remains low, indicating persistent GH resistance of hepatocytes. Whether improvement in GH secretion during treatment is due to a direct drug effect or related to the suppression of viral load could not be differentiated, as most patients demonstrated a positive virologic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
4
13
0
1
Order By: Relevance
“…In our studies, examination of serum IGF-1 concentration confirmed previous reports which observed lower concentrations in CH-C or in HCV-related liver cirrhosis, as compared to the control (25,26,29,31,32,48). Patients with chronic HCV infection manifested GH insufficiency and persistent GH resistance of hepatocytes, which may also promote a decrease in liver production of IGF-1 (48).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our studies, examination of serum IGF-1 concentration confirmed previous reports which observed lower concentrations in CH-C or in HCV-related liver cirrhosis, as compared to the control (25,26,29,31,32,48). Patients with chronic HCV infection manifested GH insufficiency and persistent GH resistance of hepatocytes, which may also promote a decrease in liver production of IGF-1 (48).…”
Section: Discussionsupporting
confidence: 77%
“…Patients with chronic HCV infection manifested GH insufficiency and persistent GH resistance of hepatocytes, which may also promote a decrease in liver production of IGF-1 (48). In patients with HCV-related cirrhosis, it was even demonstrated that the reduction in IGF-1 level preceded the diagnosis of HCC by 9.3±3.1 months (29).…”
Section: Discussionmentioning
confidence: 94%
“…This finding was supported by authors who found that transaminases have not correlated with growth hormone concentrations before or during therapy [33]. However, our observation found a significant positive correlation between growth hormone and pre-treatment ALT concentration in responder subjects and infected patients.…”
Section: Discussionsupporting
confidence: 78%
“…They added that basal and stimulated growth hormone concentrations increased significantly during antiviral therapy [33][34][35]. Some of them added that there was high significant increase of GH in responders compared to nonresponders after treatment [35].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that GH1 in HCV German [13] and Egyptian [14] patients was significantly decreased and increased significantly after antiviral therapy with interferon. Growth hormone (GH1) resistance is present in chronic liver disease (CLD) from the early stages.…”
Section: Introductionmentioning
confidence: 99%